ALTERNATIF PENGEFEKTIFAN PIDANA NON PENJARA DALAM PENANGANAN TINDAK PIDANA NARKOTIKA SEBAGAI UPAYA PENCEGAHAN OVERCROWDING RUMAH TAHANAN (STUDI DI RUTAN KELAS 1 LABUHAN DELI) - Sitorus, Jeri Fransisco; Ekaputra, Ekaputra; Marlina, Marlina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: The emergence of ideas regarding alternatives to effective punishment other than imprisonment for perpetrators of narcotics crimes is needed to prevent overcrowding. The formulation of the problems discussed are how the regulation of non-prison criminal law in various provisions of Indonesian criminal law; how the enforcement of narcotics laws for perpetrators of narcotics crimes affects the occurrence of overcrowding; how the application of non-prison criminal law for perpetrators of narcotics crimes is related to the occurrence of overcrowding (Study at Class 1 Labuhan Deli Prison). This study uses a normative legal research method that is descriptive analytical. Using a legislative and conceptual approach which is then systematized with primary data and secondary data obtained through field studies and literature studies. The data is then analyzed qualitatively. The regulation of non-prison criminal law has been regulated in the provisions of legislation in Indonesia, including in the form of fines, conditional sentences, rehabilitation, job training, supervision, probation, house arrest and community service. Keywords: Alternative, Prison, Criminal Act, Narcotics Abstrak: Munculnya pemikiran mengenai alternatif pengefektifan pemidanaan selain pidana penjara bagi pelaku tindak pidana narkotika diperlukan untuk mencegah terjadinya overcrowding. Rumusan masalah yang dibahas yaitu bagaimana pengaturan hukum pidana non penjara dalam berbagai ketentuan hukum pidana Indonesia; bagaimana penegakan undang-undang narkotika bagi para pelaku tindak pidana narkotika dalam mempengaruhi terjadinya overcrowding; bagaimana penerapan pidana non penjara bagi para pelaku tindak pidana narkotika kaitannya dengan terjadinya overcrowding (Studi di Rutan Kelas 1 Labuhan Deli). Menggunakan pendekatan perundang-undangan dan konseptual yang kemudian mensistematiskannya dengan data primer dan data sekunder yang didapat melalui studi lapangan dan studi kepustakaan. Data kemudian dianalisis secara kualitatif. pengaturan hukum pidana non penjara telah diatur dalam ketentuan perundang-undangan di Indonesia, diantaranya berbentuk pidana denda, pidana bersyarat, rehabilitasi, pidana pelatihan kerja, pidana pengawasan, pidana percobaan, tahanan rumah dan pelayanan masyarakat. Kata kunci: Alternatif, Penjara, Tindak Pidana, Narkotika